ASIA RAPIDLY AGING OUTLOOK: A SOCIOLOGICAL APPRAISAL - Sheykhi, Mohammad Taghi (Acta Scientiae et Intellectus, 2024)
Overall socio-economic change in Asia since 1960s has highly contributed to population aging of the region. Many Asian countries are currently experiencing it. While some have well planned it, many are trapped. Socio-economic modernization of the region has affected the demographic characteristics of many Asian nations including Iran. The research explores the need to develop a better understanding of the phenomenon. While the family network is rapidly changing, and at the same time aging is appearing within both genders, the countries of the continent must be more equipped with professional services for the increasing elderly. Overall, population aging being one of the major achievements of the 20th century, it needs appropriate sociological assessment. However, issues stemming from family relations, health services, retirement, and economic well-being of the aging population are sociologically appraised in the present article. The research identifies how the emerging aging population need special policies and due strategies to be designed and operationalized. Keywords: Elderl